PERANCANGAN SISTEM INFORMASI NOTA PENCAIRAN DANA BERBASIS WEB DI KECAMATAN MANDALAJATI KOTA BANDUNG - Fenny Kurniati; Hani Hatimatunnisani; Arlinda Septiani (Jurnal Teknologi Komputer dan Informatika, 2022)
This study aims to determine the information system for disbursement notes in Mandalajati District, Bandung City. The method used by the author is a qualitative method with a descriptive data approach, where the data collection techniques used include observation, literature study, and interviews. The system development method used is the Waterfall model, with modeling tools, namely Flowmaps, context diagrams, DFD (Data Flow Diagrams), and databases. From the research conducted, there are deficiencies in the disbursement system, which is still manual and requires time for approval of disbursement of funds. So that with Web-based programming, the authors hope to develop a system capable of integrated loading using MYSQL. This program is expected to simplify the work from the input process to disbursement reports to make it more effective and efficient.